1991
DOI: 10.1177/106002809102500215
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Quinolone—Theophylline Interactions

Abstract: Several fluoroquinolones currently under investigation or on the market potentially interact with theophylline. In this study, meta-analysis methodology was used to evaluate the significance of findings from quinolone-theophylline interaction studies. Two major databases were searched: Index Medicus (from 1986 to March 1990) and Current Content/Clinical Medicine (from 1985 to March 1990). A total of 32 studies were retrieved; 20 of these met the inclusion criteria. With a large effect size (ES) value of 2.26, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Consistent with previous investigations, we found that ciprofloxacin causes a significant increase in theophylline AUC (mean ϭ 45%); individual AUCs increased by 15 to 77% (10,17). Clarithromycin resulted in a mean increase in theophylline AUC of 8% (P Ͼ 0.05); the range was a 24% decrease to a 46% increase (Fig.…”
supporting
confidence: 91%
“…Consistent with previous investigations, we found that ciprofloxacin causes a significant increase in theophylline AUC (mean ϭ 45%); individual AUCs increased by 15 to 77% (10,17). Clarithromycin resulted in a mean increase in theophylline AUC of 8% (P Ͼ 0.05); the range was a 24% decrease to a 46% increase (Fig.…”
supporting
confidence: 91%
“…The magnitude of the interaction depends on the specific quinolone and the dosage. Lomefloxacin and fleroxacin do not appear to alter theophylline pharmacokinetics (Parent & LeBel 1991). Clinically significant interactions with the last two drugs are unusual.…”
Section: Methylxanthinesmentioning
confidence: 91%
“…A meta-analysis by Parent and LeBel (1991) determined the significance of the decreased theophylline clearance observed with individual quinolones. Enoxacin and ciprofloxacin gave the strongest evidence of an interaction with theophylline.…”
Section: Theophyllinementioning
confidence: 99%